The Description of Mental Status (Stress, Anxiety, and Depression) on Post Earthquake Victims Based on the Development Period (Adolescence, Adult, and Elderly) in Desa Pendua Kabupaten Lombok Utara - Haqi, Muhammad Hadiyanul; M.Has, Eka Mishbahatul; Bahiyah, Khoridatul (Universitas Airlangga, 2019)
Introduction: Disasters bring tremendous negative effects to all aspects of human life. The limitation personal, material, and social resources are much associated with the low functioning and psychological adjustment of post disaster individuals. The purpose of this study was to explain of mental status (stress, anxiety, and depression) in post earthquake victims based on development period (adolescents, adults, and the elderly) in DesaPenduaKabupaten Lombok Utara.Method: This research uses descriptive research design with cross sectional approach. This study uses proportional stratified sampling technique to obtain a sample of 125 people. Variables in this study were stress, anxiety, and depression. The instrument in this study used DASS 21.The research data was processed and analyzed by descriptive method and displayed in the frequency distribution table.Result: The most age group of adolescents had mild stress as many as 11 people (41%), most adult groups had moderate stress as many as 29 people (39%), the most elderly group in moderate stress was 11 (46%).Conclusion: Mental status conditions that are commonly found after disasters in all age groups are stress and anxiety. Therefore, it is expected that korban gempats can care more about physical and psychological health by visiting routine health check-ups and the most important thing is fulfilling basic needs of individuals such as food, exercise and adequate rest and more spiritual activities so the korban gempats could avoid physical and psychological problems after the disaster.